KONTRUKSI MOTHERHOOD DALAM IKLAN DETERGEN DI MEDIA MASSA - Ma'ruf Chandra Utama; Eriska Nanda Pratiwi; Azamudin Syair Ariviandra (Sintesa, 2026)
This study examines the construction of the motherhood concept in Indonesian television detergent advertisements. The research method is qualitative descriptive with content analysis of five popular detergent advertisements. The findings reveal that detergent advertisements consistently and systematically represent women as the sole party responsible for domestic work, while father figures are completely absent from domestic activities or only appear as product knowledge authorities with passive roles. This relates to standpoint feminist theory, which reveals how women's epistemological perspectives on the double burden of domestic-career work are silenced by the patriarchal viewpoint of the advertising industry. Visual representations depict women with unrealistic happy expressions in private domestic settings such as kitchens, laundry areas, and family rooms, using soft pastel colors, stereotypical feminine gestures, and consistently neat physical appearances despite doing housework. Verbal narratives contain explicit slogans such as "good mother," "mother's love in every fabric strand," and "tenderness for the beloved family" that explicitly measure motherhood quality based on perfect laundry results and family clothing cleanliness. Three dominant patriarchal motherhood construction patterns were identified: domestication of women through exclusive depiction in private spaces, naturalization of the mother's role as innate responsibility and destiny through verbal narratives that normalize gender subordination, and absence of fatherly responsibility that structurally reinforces unequal gender division of labor and masculine privilege. Media representation theory illustrates how advertisements not only passively reflect social reality but actively reproduce and naturalize patriarchal ideology that systematically limits women's mobility and aspirations in public and professional spheres. Content analysis shows that these representations benefit the commodification of gender roles for commercial interests of the advertising industry. The women's standpoint perspective reveals the reality of double domestic-career burden, psychological pressure of perfect mother standards, and injustice in household work division that never appears in detergent advertisement narratives. Keywords: Motherhood; Gender Bias; Detergent Advertising; Women Representation